(untitled) (Research, Society and Development, 2022)
This study aimed to establish the relationship between antral follicle count (AFC), the time of puberty, and ovarian response in Nelore heifers subjected to timed-AI (TAI) protocols. Prepubescent Nelore heifers (Bos indicus; n = 30) were examined by transrectal ultrasound and videos of the ovaries were recorded for later CFA (≥ 3 mm). After AFC, heifers were divided into 2 groups, low and high AFC and then further ultrasonic ovarian assessments were performed to determine the onset of puberty. Once puberty was established in all heifers, they were submitted to an FTAI protocol. There were no differences (P > 0.1) between groups on the time of puberty, ovulation rate, the proportion of heifers that expressed estrus, and on preovulatory follicle diameter. However, heifers with low AFC had a smaller ovarian area in the prepubertal period (4.36 ± 0.3 vs. 5.65 ± 0.2 cm2) and, in the FTAI, they had the moment of estrus (48 ± 0.0 vs. 58.5 ± 3.1 h) and earlier ovulation (60 ± 1.8 vs. 72.6 ± 4.7 h) compared to heifers with high AFC (P < 0.05). In addition, heifers in the low AFC group had a higher (P = 0.05) pregnancy per AI (76.9%, 10/13) than the high AFC group (29.4%, 5/17). In this study, heifers with low AFC had the moment of ovulation anticipated and greater pregnancy per AI compared to heifers with high AFC.